2014
DOI: 10.1680/macr.13.00254
|View full text |Cite
|
Sign up to set email alerts
|

A study of the possibility of using TFT-LCD waste glass as an admixture for steam-cured PHC piles

Abstract: In the high-tech industry in Korea, the use of thin-film transistor liquid-crystal display (TFT-LCD) glass products has increased significantly in recent years and large amounts of TFT-LCD waste glass are produced during the manufacturing process. This research studied the effect of TFT-LCD waste glass proportions on binder in mortar when added with an appropriate amount of activator. Experiments were conducted to determine the optimal replacement content to ensure that the quality of prestressed high-strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This research gap motivated the study presented in this paper. It should be pointed out, however, that multiple attempts have been conducted to use thin-film transistor liquid-crystal display (TFT-LCD) waste glass to partially replace OPC [ 15 , 16 , 17 , 18 ]. For example, Lin et al [ 15 ] tested up to 40% of TFT-LCD waste glass to replace OPC, and concluded that as the amount of TFT-LCD waste glass increases the strength of the paste distinctly decreases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research gap motivated the study presented in this paper. It should be pointed out, however, that multiple attempts have been conducted to use thin-film transistor liquid-crystal display (TFT-LCD) waste glass to partially replace OPC [ 15 , 16 , 17 , 18 ]. For example, Lin et al [ 15 ] tested up to 40% of TFT-LCD waste glass to replace OPC, and concluded that as the amount of TFT-LCD waste glass increases the strength of the paste distinctly decreases.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lin et al [ 15 ] tested up to 40% of TFT-LCD waste glass to replace OPC, and concluded that as the amount of TFT-LCD waste glass increases the strength of the paste distinctly decreases. Jang et al [ 16 ] used additional activator to promote reactivity of TFT-LCD waste glass with OPC, and concluded that the pozzolanic reaction between the waste glass and the activator leads to enhance compressive strength of high strength concrete products. Kim et al [ 18 ] found that smaller particle size of ground TFT-LCD waste glass would lead to the decreased porosity of TFT-LCD waste glass concrete, which is expected to enhanced durability and permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Jala (2012 reported an increased concrete compressive strength using recovered waste fibres from milling and machining. Recently, Jang et al (2014) investigated the influence of adding thin film transistor liquid crystal display (TFT-LCD) waste glass with an appropriate ratio of activator on binder in mortar. The obtained results showed that utilising TFT-LCD as an admixture decreased alkali-silica reaction expansion and enhanced the workability and compressive strength of the mortars (Jang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%